An investigation into the language of affect in english remarks by political leaders at conferences on climate change in the appraisal theory - Tô Mỹ Quỳnh Châu (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This thesis focused on investigating the language of Affect (LOA) in the English remarks by leaders at conferences on climate change in the view of the Appraisal theory by Martin and White (2005). Halliday‘s functional grammar and Martin and White (2005)‘s appraisal theory are the theoretical framework for conducting this thesis. It investigated the syntactic features in terms of clause as message in the view of functional grammar, and the semantic features in terms of the un/happiness, in/security, dis/satisfaction, positive/negative affect in the view of the appraisal theory. Both qualitative and quantitative methods were used as a tool to investigate these features of the samples. It was also built for the analysis of LOA used in political remarks on the climate change at conferences in order to assist Vietnamese learners to have a deep understanding of LOA in particular or the Appraisal theory in general. The qualitative presentation of this thesis is illustrated with samples quoted from the leader‘s English remarks on climate change at conferences. More than 30 data including 214 samples extracted and collected from the official website on climate change were used to build the thesis‘s analyzing. Pedagogically, the research result can be a useful material for educators, learners of English, especially for those who are interested in teaching and learning the LOA of English remarks.